MODEL MANAJEMEN LITERASI DI SEKOLAH DASAR - Kustoro Budiarta; Ahmad Hidayat; Riza Indriani (Universitas Negeri Medan, 2023)
This study analyzes the effect of the completeness of facilities and human capital on the management of school literacy in SD Negeri Medan. The number of research samples is 150 respondents. It consists of school principals and teachers of public elementary schools in Medan City from 150 schools. Sampling was carried out using a two-stage cluster sampling technique by taking into account location factors and literacy programs in schools. Data analysis used multiple linear regression analysis and to test the hypothesis used the t test (t test) to determine the partial effect and the F test (F test) to determine the effect simultaneously. The results of the data analysis show that the research model is in the form of a nerganda linear regression equation Ŷ = 3.304 + 0.491X1 + 0.898X2 + e and the results of hypothesis testing prove that there is a positive and significant influence between the completeness of facilities on literacy management in public elementary schools in Medan City, there is a significant influence positive and significant relationship between human capital on literacy management in public elementary schools in Medan City and there is a positive and significant influence between the completeness of facilities and human capital on literacy management in public elementary schools in Medan city.